Effect of Ratio of Moringa Leaves Juice with Pineapple Juice and Arabic Gum on the Quality of Jelly Candy - Purba, Carly; Sinaga, Hotnida; Nurminah, Mimi (Indonesian Journal of Agricultural Research, 2018)
The purpose of this research was to determine the effect of ratio of moringa leaves juice with pineapple juice and the best percentage of arabic gum on the quality of jelly candy. This research was using completely randomized design with two factors, i.e. : ratio of moringa leaves juice with pineapple juice (K): (100%:0% ; 75%:25% ; 50%:50% ; 25%:75% ; 0%:100%) and arabic gum percentage (G): (1,0% ; 1,5% ; 2,0%). Parameters analyzed were moisture content, ash content, vitamin C content, total soluble solid, total acid, lightness value (L*), hedonic organoleptic values of colour, flavour, taste, texture and score organoleptic values of colour and texture. The results showed that the ratio of of moringa leaves juice with pineapple juice had highly significant effect on ash content, vitamin C content, total acid, lightness value, hedonic organoleptic test of colour, flavour, taste and score organoleptic value of colour. The ratio of moringa leaves juice with pineapple juice (25%:75%) and 2,0% arabic gum percentage produces the best quality of jelly candy based on hedonic organoleptic values of colour, flavour, taste, texture and score organoleptic values of colour and texture.